Agro-techniques for Productive and Profitable Crop Management under Excess Water Regimes - Dwibedi, S. K.; Mohanty, A. K.; Sarkar, N. C.; Sahoo, B. B. (International Journal of Bio-resource and Stress Management, 2017)
Due to climate change, the rainfall pattern has changed dramatically. Vagaries of monsoon and its unpredictable onset or withdrawal or breaks in between become a possible threat for the farmers especially in the rainfed areas. Due to differential rainfall, the rainwater stagnates in the low-lying areas. Like moisture stress or drought, excess moisture or water stagnation for a period of time needs equal attention for successful crop management. Such abiotic stress condition could be managed by two ways; firstly, growing the crops adapted with suitable agro-techniques for potential yield. Secondly, through special cultivation methods that may help to avoid excess moisture. To feed the ever burgeoning population in India due attention is to be paid for increasing the food grain production not only in arable lands but also in areas affected by excess water situations. Varietal substitution of rice with Varshadhan, Hangseswari, Swarna Sub 1 are found befitting due to ecological adaptability. System of rice intensification with more soil organics and early establishment of the rice plants could better sustain submergence under flash flood. Non-traditional crops like water chestnut, fox nut, hogla, sweet flag are very good alternatives to rice in waterlogged areas. Bio-drainage through Casuarina and land alternations through raised and sunken beds could alleviate the problems and diversify the rice-rice cropping system.